Rapid Tube Hydroforming - The Innovative Casting-Forming Method for Rapid Prototyping - Kochanski, Andrzej; Sadlowska, Hanna (Manufacturing Technology Journal, 2020)
In the recent years, the demand for weight reduction in modern vehicle construction has led to an increase in the application of hydroforming processes for production of automotive and aerospace lightweight components. The tube hydroforming measurement site (TH stand), designed and built at Warsaw University of Technology allows both die, and free tube hydroforming processes to be performed, thereby making it possible to obtain information about the material, as well as optimal process parameters [1][2]. The present freshly patented method for metal tube hydroforming is dedicated to short product series or even single products and prototypes [3]. The method is applicable to forming difficult-to-machine materials. The well-known techniques use dies made of plastic or wood, especially to form short product series. The use of moulding sand and properly prepared geometry of casting mould makes possible shaping materials at high temperatures, which could not be done in previous short series solutions, where a plastic or wooden die were used. [1] Sadlowska H., Jasinski C. Morawinski L., Strain measurements on the tube hydroforming testing machine, Archives of Metals and Metallurgy Vol. 65 , Issue 1, 2020, pp. 257-263 [2] Sadlowska H., Odksztalcanie sie rur podczas swobodnego rozpeczania hydromechanicznego na stanowisku TH, w: Prace Naukowe Politechniki Warszawskiej. Mechanika, Vol. 267, 2015, ss. 25-30 (in Polish) [3] Patent No. PL424401, Kochanski A., Sadlowska H., Bulletin of the Patent Office of Inventions and Utility Models vol. 17_2019, pp. 11
Keywords: hydroforming; casting mould; rapid prototyping; process numerical modelling